KEEFEKTIFAN MODEL TGT BERBANTUAN CD PEMBELAJARAN REKREATIF TERHADAP MOTIVASI DAN HASIL BELAJAR - Septiana, Meli; Mashuri, Mashuri; Agoestanto, Arief (Unnes Journal of Mathematics Education, 2012)
The aim of this study was to determine the effectiveness of recreational learning CD-assisted model TGT toward motivation and learning outcomes for student. The population of this study was the students of grade VIII SMP N 1 Muntilan school year 2011/2012. By using cluster random sampling technique we were obtain two groups. The groups were experiment group and control group. Questionnaire was used to obtain motivation of learning data; observation was used to obtain activity of teacher and student data; and a test was used to obtain learning outcomes for student. The results of the proportion test students learning outcomes data indicate that the experiment group had reached the mastery of learning. Test similarity of two average scores on the motivation to learn the data showed that score of motivation to study experiment group higher than the control group. Test similarity of two average of learning outcomes data show that the results of experimental study of students grade higher than the control group. Test similarity of two proportions in the learning outcome data showed that the percentage of the study of students who achieved at individual KKM of experiment group over the control group. Based on this study, it can be said that the recreational learning CD-assisted learning model TGT was effective toward learning motivation and learning outcomes of students in subject matter prism and pyramid.